Ethical Socialism and the Trade Unions: Allan Flanders and British Industrial Relations Reform - Hyman, Richard (Relations industrielles / Industrial Relations, 2011)
Ethical Socialism and the Trade Unions: Allan Flanders and British Industrial Relations Reform, by John Kelly, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Ethics; Labor Unions; Reforms; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Socialism